Micro end milling of AISI 304 stainless steel and analysis of micro surface roughness - Ali, Mohammad Yeakub; Khan, Ahsan Ali; Othman, Khairul Irman; Omar, Mohd Aliff (2009)
This paper discusses tool based micromilling of AISI 304 to generate micro surface roughness. The aim is to have lowest roughness average (Ra) and also lowest maximum height of the surface (Rmax). Feed per tooth, cutting speed and coolant were chosen as the cutting parameters for the investigation. Using a 500 μm diameter tungsten carbide end milling tool 18 experiments were conducted with and without the application of coolant. Empirical models for estimation of Ra and Rmax are developed and verified. The models showed that the feed rate and cutting speed both directly and interactively influence the surface roughness. The optimized values of feed rate and cutting speed are found to be 1 μm and 78 mm/s respectively.